2006
DOI: 10.1111/j.1460-9592.2006.02119_7.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Bis Assessment of Sedation in Paediatric Intensive Care – Two case Reports

Abstract: The notes of these neonates were reviewed for the following information: birth weight, gestational age, co-existing congenital anomalies, preoperative respiratory function, operation duration, postoperative analgesia, ICU admission and duration of stay in ICU. Results: Thirty-five TOF repairs were identified. One neonate was excluded as he had concomitant abdominal surgery. Of the 34 remaining, 30 sets of notes were reviewed. The outcome for these neonates is shown in the diagram. Of the 10 neonates who did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The maximum duration of these asymmetries was < 5 min. The median (IQR [range]) number of intra-operative BIS asymmetries per patient with BIS asymmetry was 3 (2-5 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). The median (IQR [range]) number of intra-operative BIS asymmetries per hour of surgery in these patients was 1.5 (1.1-2.4 [0.3-5.1]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum duration of these asymmetries was < 5 min. The median (IQR [range]) number of intra-operative BIS asymmetries per patient with BIS asymmetry was 3 (2-5 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). The median (IQR [range]) number of intra-operative BIS asymmetries per hour of surgery in these patients was 1.5 (1.1-2.4 [0.3-5.1]).…”
Section: Resultsmentioning
confidence: 99%
“…However, no studies focussed on this relationship have been performed. Handedness and cerebral hemisphere dominance may not be fully developed in small children and brain structures determining handedness and cerebral hemisphere dominance may not be involved in the generation of EEG components determining BIS values [3–8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, one of the authors (C.A.M.) who presented initial data from our study at an international forum 12 reported the occurrence of BIS asymmetry in children sedated in PICU.…”
mentioning
confidence: 99%